2006
DOI: 10.1515/bmt.2006.018
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung der Setzkraft für die Sicherheit einer Konuskopplung von Hüftstiel und keramischem Prothesenkopf / Relevance of the insertion force for the taper lock reliability of a hip stem and a ceramic femoral head

Abstract: In endoprosthetics alumina ceramic femoral heads have been established for many years and their outstanding wear characteristics are scientifically proven. The taper connection between the hard but brittle ceramic head and the metallic stem must be performed by the operating surgeon intraoperatively. Thereby it is left to the surgeon to interpret imprecise and strongly deviating instructions given from manufacturer to manufacturer. This study clarifies the enormously large variations of interpretation in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 5 publications
3
24
0
Order By: Relevance
“…In both models, the fixation force correlates linearly with the force applied to impact the taper. The fixation force, therefore, has a major effect on the stability of the taper connection [6,[44][45][46][47][48][49][50][51][52]. Because the taper angle α is determined by the chosen prosthesis design (typically between 5 • 30 and 6 • [36]), this parameter has to be considered as fixed.…”
Section: Technical Aspects Of Taper Connections In Hip Arthroplastymentioning
confidence: 99%
See 2 more Smart Citations
“…In both models, the fixation force correlates linearly with the force applied to impact the taper. The fixation force, therefore, has a major effect on the stability of the taper connection [6,[44][45][46][47][48][49][50][51][52]. Because the taper angle α is determined by the chosen prosthesis design (typically between 5 • 30 and 6 • [36]), this parameter has to be considered as fixed.…”
Section: Technical Aspects Of Taper Connections In Hip Arthroplastymentioning
confidence: 99%
“…Impaction with at least 4000 N is recommended. An adequate impaction force can be reached with a strong blow from a 500 g hammer [46,50]. Surgeons should become familiar and proficient with force-measuring instruments, especially those surgeons with low levels of experience in arthroplasty, to avoid the application of insufficient or off-axis impaction force [46].…”
Section: Surgeon-related Factors Determining Taper Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it must be assumed that such a hammer blow is performed very individually by the surgeon and is therefore not reproducible. This is illustrated by Nasutt et al [16] who compared the assembly forces resulting from hammer blows of 39 surgeons. It was shown that the force varies between 0.27 kN and 7.85 kN [16].…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated by Nasutt et al [16] who compared the assembly forces resulting from hammer blows of 39 surgeons. It was shown that the force varies between 0.27 kN and 7.85 kN [16]. However, these were only trials on a test rig, so it must be assumed that the absolute values in surgery are different due to soft tissue damping.…”
Section: Introductionmentioning
confidence: 99%